Stoichiometry deviation in amorphous zirconium dioxide. Issue 29 (24th May 2019) - Rushton, Michael J. D.; Ipatova, Iuliia; Evitts, Lee J.; Lee, William E.; Middleburgh, Simon C.
Abstract : The accommodation mechanism for excess oxygen in amorphous ZrO2 is identified using state-of-the-art methods: employing reverse Monte-Carlo, molecular dynamics and density functional theory together. Excess oxygen is predicted to enter amorphous ZrO2 exothermically from O2 . Abstract : Amorphous zirconia (a-ZrO2 ) has been simulated using a synergistic combination of state-of-the-art methods: employing reverse Monte-Carlo, molecular dynamics and density functional theory together. This combination has enabled the complex chemistry of the amorphous system to be efficiently investigated. Notably, the a-ZrO2 system was observed to accommodate excess oxygen readily – through the formation of neutral peroxide (O2 2− ) defects – a result that has implications not only in the a-ZrO2 system, but also in other systems employing network formers, intermediates and modifiers. The structure of the a-ZrO2 system was also determined to have edge-sharing characteristics similar to structures reported in the amorphous TeO2 system and other chalcogenide-containing glasses.